2007
DOI: 10.1016/j.mce.2006.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The structures that underlie normal reproductive function

Abstract: The mechanisms and physiology of reproductive function have fascinated scientists throughout time. Recent cellular and molecular level structural studies have provided unprecedented insights into reproductive systems and signaling networks. This 'cutting edge' editorial provides a recent example in each of these areas, namely, the anatomical integrity of the follicle, the molecular structure of activin with its binding partners and the molecular regulation of inhibin. These three examples of structure informin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Model building was performed using O (43), and figures were generated using PyMol. 4 Fluorescence Polarization-Fluorescence polarization assays were performed at Northwestern University's Keck Biophysics Facility on a Beacon 2000 (Invitrogen). Assays were performed at 1 nM fluorescein-labeled heparin (Invitrogen) and were repeated at least three times in triplicate, carried out in 20 mM HEPES buffer (pH 7.0) with 0.1% Triton X-100 and 150 mM or 250 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model building was performed using O (43), and figures were generated using PyMol. 4 Fluorescence Polarization-Fluorescence polarization assays were performed at Northwestern University's Keck Biophysics Facility on a Beacon 2000 (Invitrogen). Assays were performed at 1 nM fluorescein-labeled heparin (Invitrogen) and were repeated at least three times in triplicate, carried out in 20 mM HEPES buffer (pH 7.0) with 0.1% Triton X-100 and 150 mM or 250 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Activin A, a member of the TGF␤ superfamily, is necessary to the regulation of both the male and the female reproductive axes by stimulating the release of follicle-stimulating hormone from the pituitary (4,5). Activin A also has other important physiological roles, because activin A-deficient mice die shortly after birth and exhibit multiple defects in craniofacial development (6,7).…”
mentioning
confidence: 99%
“…Besides zebrafish, six splice variants of alternatively spliced grass carp ActRIIA have been cloned and characterized (Chen et al, 2009). Activin receptors (RIIA and RIIB) being the central element for a wide range of TGF-β ligands elicit numerous cellular and biological activities both at paracrine and autocrine level (Lerch et al, 2007). Existing knowledge about the role of ActRIIA in fish is limited; identification and characterization of more number of fish activin receptors is necessary for understanding the mechanism underlying the biology of the receptor functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin being the potent negative regulator of growth is involved in regulating skeletal muscle mass in vertebrates (McPherron et al, 1997;Lee and McPherron, 2001). Similarly, other ligands like activin and its negative regulator inhibin have also shown to have effect on fish reproduction during oocyte maturation and FSH release (Lerch et al, 2007;Petrino et al, 2007). However, growth curve in fishes is dependent more or less on the reproductive cycle and the interaction between growth and reproduction in fishes is a major link that appears to be really particular for fish physiological actions (Jalabert, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also indicated a further disadvantage associated with the use of higher eukaryotic cell lines that inherently produce activin, namely, the presence of strong binding partners, such as the follistatins, for the activin A protein. 31 Furthermore, insect cells producing activin A have a more rapid rate of lysis than other cells, a possible consequence of the role of activin A in apoptosis. 29 Although it would be ideal to produce recombinant activin A in an easily manipulated and inexpensive microbial expression system, bacterial expression is not an option since these micro-organisms cannot perform the post-translational modifications necessary to generate the precursor pre-pro-activin A with the correct level of glycosylation and directed disulphide bond formation.…”
Section: Introductionmentioning
confidence: 99%